2018
DOI: 10.1103/physrevd.98.064043
|View full text |Cite
|
Sign up to set email alerts
|

Geometric horizons in the Kastor-Traschen multi-black-hole solutions

Abstract: We investigate the existence of invariantly defined quasi-local hypersurfaces in the Kastor-Traschen solution containing N charge-equal-tomass black holes. These hypersurfaces are characterized by the vanishing of particular curvature invariants, known as Cartan invariants, which are generated using the frame approach. The Cartan invariants of interest describe the expansion of the outgoing and ingoing null vectors belonging to the invariant null frame arising from the Cartan-Karlhede algorithm. We show that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 74 publications
(147 reference statements)
1
12
0
Order By: Relevance
“…its behavior at null spatial infinity, for locating its horizon(s) which can therefore be observed by experimental devices of finite sizes, taming its teleological nature pointed out in [43,44]. Therefore, we have explicitly shown that the horizon constitutes a local property of the manifold (in agreement with the core principles of any relativistic field theory), and that a curvature invariant can be constructed for its detection once the geometrical symmetries of the spacetime are known regardless the gravitational theory behind it: this is consistent with the geometric horizon conjecture [40,[45][46][47][48][49][50][51][52][53]. On the other hand, our results are important also from the practical point of view in light of the so-called excision technique in numerical relativity: the black hole horizon constitutes a causal boundary separating the evolutions of phenomena occurring outside it from what it may happen inside; thus, the spacetime region delimited by the horizon must be removed (or excised) when performing numerical simulations of the evolution of a black hole.…”
Section: Curvature Syzygyssupporting
confidence: 82%
“…its behavior at null spatial infinity, for locating its horizon(s) which can therefore be observed by experimental devices of finite sizes, taming its teleological nature pointed out in [43,44]. Therefore, we have explicitly shown that the horizon constitutes a local property of the manifold (in agreement with the core principles of any relativistic field theory), and that a curvature invariant can be constructed for its detection once the geometrical symmetries of the spacetime are known regardless the gravitational theory behind it: this is consistent with the geometric horizon conjecture [40,[45][46][47][48][49][50][51][52][53]. On the other hand, our results are important also from the practical point of view in light of the so-called excision technique in numerical relativity: the black hole horizon constitutes a causal boundary separating the evolutions of phenomena occurring outside it from what it may happen inside; thus, the spacetime region delimited by the horizon must be removed (or excised) when performing numerical simulations of the evolution of a black hole.…”
Section: Curvature Syzygyssupporting
confidence: 82%
“…To address this, a new set of curvature invariants has been introduced that are adapted to the interpretation of QS Szekeres PBH solutions. In addition to showing that the apparent horizon is detected by the vanishing of a Cartan invariant, implying that it is a geometric horizon [9,10,11], we have also introduced invariants to characterize the expansion or contraction of spacetime itself, the spatial rate of change and extrema of the areal radius, the spatial rate of change and extrema of the mass function, the relative movement of matter shells, the existence of shell-crossings and regular spatial extrema in a QS Szekeres solution. We note that this new set of invariants can describe the evolution of any QS Szekeres dust models and has a physical interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…To show that R = 2M is a geometric horizon, we note that the extended Cartan invariant ρ, defined in equation ( 14), will vanish on the surface R = 2M [9,10]. This surface is a dynamical geometric horizon since the extended invariant, µ, which also appears in the covariant derivative of the curvature tensor, is negative within the surface R = 2M [11]. The spin-coeficients ρ and µ correspond to the expansion of the ingoing and outgoing null directions; i.e., ρ = θ ( ) and µ = θ (n) .…”
Section: Detection Of the Horizonmentioning
confidence: 99%
See 2 more Smart Citations